Genetic Variation, Diversity and Genotype by Environment Interactions of Nutritional Quality traits in East African Sweetpotato - Tumwegamire, S. (2011)
Sweetpotato is one of the staples that have been earmarked by the global initiatives to fight micronutrient eficiency, particularly vitamin A deficiency. The present study sought to contribute to the pre-breeding knowledge base required for the improvement of sweetpotato nutritional quality targeting β-carotene, dry matter, starch, sucrose and minerals (i.e Fe, Zn, Ca and Mg) as a sustainable strategy to reduce the problems associated with the micronutrient deficiencies and malnutrition among people in developing countries. The specific objectives of the study were to i) characterize selected East African sweetpotato accessions for storage root quality (dry matter, protein, starch, sucrose, ß-carotene, iron, zinc, calcium and magnesium) ii) determine the magnitude of GxE variation in orange-fleshed sweetpotato (OFSP) varieties of East African origin for yield and nutritional traits conducted across ecogeograhic zones of Uganda; and iii) study genetic relationships among and between OFSP and white-fleshed sweetpotato (WFSP) farmer varieties gene pools, and how these two phenotypic groups compare with non-African OFSP and WFSP accessions. For the micronutrient profiling study, 89 (White/cream- and orange-fleshed) landraces, plus one introduction, Resisto, were evaluated at Namulonge and Kachwekano research stations in Uganda. Roots were analyzed for β-carotene, iron, zinc, calcium, magnesium, protein and starch content using the Near Infrared Refractance Spectroscopy (NIRS) procedure. The 2  G variance was significant (p < 0.01) for all the traits except sucrose content. Overall, the farmer varieties had higher dry matter, higher starch, and lower sucrose contents than the check. It is these qualities that make sweetpotato attractive as a starchy staple in EA. A low population’s mean of β-carotene content was observed. However, deep orange-fleshed farmer varieties, ‘Carrot_C’, ‘Ejumula’, ‘Carrot Dar’, ‘Mayai’ and ‘Zambezi’ had β-carotene content that can meet ≥350% of recommended daily allowance (RDA) with 250 g serving to a 5 – 8 year old child. More, but light orangefleshed farmer varieties ‘ARA244 Shinyanga’, ‘HMA493 Tanzania’, ‘K-118’, ‘K-134’, ‘K-46’, ‘PAL161’, ‘Sowola6’, ‘SRT52’, and ‘Sudan’ can provide 50 - 90% RDA of the child. The root minerals’ content was generally low except for magnesium, the content of which can meet ≥ 50% RDA in many farmer varieties. However, in areas with high sweetpotato consumption, varieties ‘Carrot_C’, ‘Carrot Dar’, ‘KRE Nylon’, ‘MLE163 Kyebandula’ and ‘SRT49 Sanyuzameza’ can improve iron, zinc, calcium, and magnesium intake. In conclusion, some EA farmer varieties can contribute greatly to alleviation of vitamin A deficiency and meaningful mineral intakes. The GxE analysis was conducted with regression, and additive main effects and multiplicative interaction (AMMI). The environment effects were significant (p < 0.05; or < 0.01) for root yield, harvest index, and all quality traits except dry matter. The genotypic effects were significant (p < 0.05; or < 0.01) for all traits except root yield, iron and magnesium. Accessions, ‘Ejumula’, ‘SPK004/6’, and ‘SPK004/6/6’ had higher root yields than the check, Resisto, while ‘Naspot_5/50’ had the lowest root yields. The former three accessions are released in Uganda, and represent the potential gains in breeding for orange-fleshed sweetpotato clones with high root yields, dry matter and β-carotene. The σ2 GxE components were not significant (p>0.05) for βcarotene and starch root content. The σ2 GxE components were highly significant (p<0.01) for dry matter but fractional (0.4) compared to the corresponding σ2 G component. These results suggest traits can be improved with high selection efficiency in the early stages of a sweetpotato breeding program. The σ2 GxE: σ2 G ratio was close to 1 for harvest index and sucrose content, and large (> 2) for storage root yields and all mineral contents. Like for yield, the results suggest that breeding for elevated mineral levels in sweetpotato is complex and requires information about the causes of GxE interactions before the breeder can embark on enhancing these minerals. However, medium to high positive correlations among mineral traits simplify selection aiming at elevated mineral contents in sweetpotato and it merits research if the trait complex of minerals can be improved more efficiently by an index. For the genetic diversity study, eighty five East African farmer varieties (29 OFSPs and 56 WFSPs) and 7 varieties of non-African origin as check clones were analyzed using 26 simple sequence repeat (SSR) markers. A total 158 alleles were scored with an average of 6.1 alleles per SSR loci. The mean of Jaccard’s similarity coefficients was 0.54. The unweighted pair group method analysis (UPGMA) revealed a main cluster for EA germplasm at a similarity coefficient of 0.52. At a similarity coefficient of about 0.56 sub clusters within the EA germplasm were observed, but these were neither country nor flesh color specific. Analysis of molecular variance (AMOVA) found a significant difference between EA and non-African germplasm, and a non significant difference between OFSP and WFSP germplasm. In conclusion, the EA germplasm appears to be distinct from non-African germplasm, and OFSP and WFSP farmer varieties from EA are closely related. OFSP farmer varieties from EA might show similar adaptation to SSA environments as WFSP and a big potential in alleviating vitamin A deficiency (VAD).